Assessment of pharmacotherapeutic safety of medical prescriptions for elderly residents in a long-term care facility - Fabiana Rossi Varallo; Ingrid Stephanie Stein Ambiel; Luana Orlandelli Nanci; José Carlos Fernandes Galduróz; Patricia de Carvalho Mastroianni (Universidade de São Paulo, 2012)
The present study aimed to estimate the prevalence of elderly using potentially inappropriate medications (PIM) and with occurrence of potentially hazardous drug interactions (PHDI); to identify the risk factors for the prescription of PIM and to evaluate the impact of pharmaceutical intervention (PI) for the prescription of safer therapeutic alternatives. Therefore, a cross-sectional study was performed in a long-term care facility in São Paulo State, between December/2010 and January/2011. The medical records of the patients >60 years old who took any drugs were consulted to assess the pharmacotherapeutic safety of the medical prescriptions, in order to identify PIM and PHDI, according to the Beers (2003) and World Health Organization criteria, respectively. PI consisted of a guidance letter to the physician responsible for the institution, with the suggestions of safer equivalent therapeutics. Approximately 88% of the elderly took at least one drug, and for 30% of them the PIM had been prescribed. Most of the PIM identified (53.4%) act on the central nervous system. Among the 13 different DI detected, 6 are considered PHDI. Polypharmacy was detected as a risk factor for PIM prescription. After the PI there was no change in medical prescriptions of patients who had been prescribed PIM or PHDI. The data suggests that PI performed by letter, as the only interventional, method was ineffective. To contribute it a wide dissemination of PIM and PHDI among prescriber professionals is necessary for the selection of safer treatment for elderly. Additionally, a pharmacist should be part of the health care team in order to help promote rational use of medicines. O presente estudo teve como objetivos estimar a prevalência de idosos em uso de medicamentos potencialmente impróprios (MPI) e com ocorrência de interações medicamentosas potencialmente perigosas (IMPP); identificar os fatores de risco para a prescrição de MPI e avaliar o impacto de intervenção farmacêutica (IF) para a prescrição de alternativas terapêuticas mais seguras. Para tanto, realizou-se estudo transversal em instituição de longa permanência do interior de São Paulo, de dezembro/2010 a janeiro/ 2011. Os prontuários médicos dos pacientes >60 anos e que utilizavam pelo menos um medicamento foram consultados para avaliar a segurança farmacoterapêutica das prescrições médicas, identificando-se os MPI e as IMPP, segundo critérios de Beers (2003) e o critério da Organização Mundial da Saúde, respectivamente. A IF constou de carta de orientação ao médico da instituição, com sugestão de equivalentes terapêuticos mais seguros. Aproximadamente 88% dos idosos haviam utilizado pelo menos um medicamento e, para 30% deles, havia pelo menos um MPI prescrito. A maioria dos MPI identificados (53,4%) age no sistema nervoso central. Entre as 13 interações medicamentosas detectadas, 6 são consideradas IMPP. A polimedicação foi detectada como fator de risco para a prescrição de MPI. Após a IF, não houve alterações nas prescrições médicas dos pacientes que apresentavam MPI e IMPP prescritos. Os dados sugerem que IF realizadas por cartas, como único método interventivo, não são efetivas. Para contribuir com a seleção de farmacoterapia mais segura para idosos é necessária ampla divulgação dos MPI e IMPP entre os profissionais prescritores. Além disso, o farmacêutico deve fazer parte das equipes de saúde para auxiliar na promoção do uso racional de medicamentos.